Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Guru (Studi Kasus : SD Alam Baiturrahman Bontang) - Mujahidin, Umar Shiddiq; Isharyani, Muriani Emelda; Gunawan, Suwardi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to determine and analyze the influence of the Work Environment and Work Motivation on the Performance of SD Alam Baiturrahman Bontang Teachers. The type of research used in this study is quantitative. The data analysis method used is multiple linear regression. The population in this study were SD Alam Baiturrahman Bontang Teachers, the number of samples in this study was 30 teachers. Based on the results of hypothesis testing in this study, the Work Environment variable does not affect the Performance of SD Alam Baiturrahman Bontang Teachers, while the Work Motivation variable affects the Performance of SD Alam Baiturrahman Bontang Teachers. Simultaneously or together, the Work Environment and Work Motivation variables affect the Performance of SD Alam Baiturrahman Bontang Teachers. The determination coefficient (R2) value is 0.406 or 40.6%. This shows that the work environment and work motivation are able to explain 40.6% of teacher performance. While the remaining 59.4% is influenced by other variables not examined in this study.